The arrangement of spatial settlement for Balinese and Sasak communities at historical perspective in Cakranegara - Widana, I Nyoman Murba; Julianingsih, L. P. Eka M.; Wirawan, I Wayan Ardhi (Research Journal in Advanced Humanities, 2023)
This study aims to examine the construction of a social integration model through the arrangement of resident spaces in the Balinese-Hindu and Sasak-Islam communities in the Cakranegara territory, Lombok. This research was designed in a qualitative interpretative research type with the religious anthropological approach. There are three findings in response to the focus of this research study. First, the residential spaces of Balinese-Hindu community settlements are arranged in territorial blocks called karang. Each karang has a name identical to the name of the region where it originated in Bali. Second, the residential spaces pattern of the Cakranegara area during the kingdom period used the basic concept of Hindu religious teachings, namely by taking the bhuana Agung spaces concept (macrocosm) which represented the tri angga. Third, the Sasak-Islamic community during the Karangasem Kingdom in Lombok was placed outside the Balinese-Hindu community.